An update on rapid universal neonatal hearing screening using a fast automatic auditory brainstem response device - Wilson, Wayne; Bradley, Andrew; Petoe, Matthew; Smith, Andrew; Moon, Jackie; Dzulkarnain, Ahmad Aidil Arafat (2010)
This paper provides an update on ongoing attempts to reduce the time required to complete an automated auditory brainstem response (AABR) assessment for the purposes of Universal Newborn Hearing Screening (UNHS). 492 ABR waveforms were recorded from 126 neonates who had already passed a standard UNHS assessment were re-assessed using a standard click stimulus presented at 33 and 90 cps, and click stimuli presented using a standard maximum length sequence (lMLS) with linear reconstruction and a new MLS (nlMLS) with non-linear reconstruction each presented at 90, 125, 250 and 418 cps (maximum). All stimuli were presented at 35 dBnHL and all waveforms were detected using the Fsp technique at a 99% confidence level. The median times to waveform detection for the standard clicks were 94.14 s at 33 cps and 14.76 s at 90 cps, for the lMLS clicks were 6.62 s at 90 cps, 15.44 s at 125 cps, 6.54 s at 250 cps and 4.18 s at 418 cps, and for the nlMLS clicks were 14.81 s at 90 cps, 11.7 s at 125 cps, 4.36 s at 250 cps and 3.59 s at 418 cps. Some, but not all, of these times were significantly different at the 5% level. The nlMLS clicks provided the shortest times to ABR waveform detection, with the best median time to detection being the 3.59 s provided by the nlMLS stimulus at 418 cps. The nlMLS stimulus combined with the Fsp signal detection technique holds significant promise as a method of significantly reducing the time required to perform UNHS in the clinical setting.